The Influence of Regional Original Income (PAD) and Remaining Budget Financing (SiLPA) on Economic Growth with General Allocation Funds (Dau) as Moderating Variables in Regency/City Governments in North Sumatra Province in 2011-2015 - Dita Diastrina (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2021)
This study aims to identify and analyze whether revenue (PAD) and Surplus Financing Articles (SiLPA) effect on economic growth by the General Allocation Fund (DAU) as moderating variables. The study population was the District / City in the province of North Sumatra. The method of this thesis is a descriptive statistical analysis, classic assumption test, test hypotheses and residual test. Independent variables in this study is revenue (PAD) and Surplus Financing Articles (SiLPA), while the dependent variable is economic growth and moderating variable is the General Allocation Fund (DAU) with Total population of this research are 33 districts / cities using purposive sampling obtained 18 districts / cities as samples from 2013 to 2015. the type of data used is secondary data. The results of this study demonstrate that, in the original income (PAD) and Surplus Financing Articles (SiLPA) have a significant effect on economic growth at the Regency / City in the province of North Sumatra. In partial revenue (PAD) has a significant effect on economic growth, while Budget Financing Surplus (SiLPA) has no effect and no significant effect on economic growth in the Regency / City in the province of North Sumatra. General Allocation Fund (DAU) can moderate revenue (PAD) on economic growth, while the financing Budget Surplus, DAU can not moderate relations to economic growth. while Budget Financing Surplus (SiLPA) has no effect and no significant effect on economic growth in the Regency / City in the province of North Sumatra. General Allocation Fund (DAU) can moderate revenue (PAD) on economic growth, while the financing Budget Surplus, DAU can not moderate relations to economic growth. while Budget Financing Surplus (SiLPA) has no effect and no significant effect on economic growth in the Regency / City in the province of North Sumatra. General Allocation Fund (DAU) can moderate revenue (PAD) on economic growth, while the financing Budget Surplus, DAU can not moderate relations to economic growth.